Gender Differences in Language Use under Descriptive Perspective and Qur’anic Moral Values Education - Nur Azmi Alwi; Irwandi Irwandi (Yayasan Keluarga Guru Mandiri, 2022)
Studies on the differences in the use of language by men and women are indeed very limited when viewed from a purely biological tendency. In fact, many studies have found that men's language is different from women's language socio-politically and culturally. This difference is constructed by the social order that is closely related to the problem of domination of power in the relationship between men and women. The study of gender differences in language under descriptive perspective aims to reveal the facts of social life in term of differences in roles and relations between women and men in the use of language. In addition, this research also discusses the perspective of moral values education, especially those from the Qur'an regarding the differences between women and men in terms of language use.